Experimental Study on the Spray and Self-Excitation Oscillation Characteristics of Gas-Centered Coaxial Injectors - Liu, Lu-Hao; Han, Yi-Fan; Zhang, Shao-Qing; Fu, Qing-Fei (Frontiers in Energy Research, 2022)
The present article studies the spray and self-oscillation characteristics of liquid sheets generated by a series of gas-centered coaxial injectors. An experimental system has been built to investigate the impacts of gaseous core size and recess length on the breakup and self-oscillation features. The results reveal that the gaseous flow shows an apparent impact on the liquid sheet breakup length with a small gaseous core size. The atomization morphology shows the different patterns under varied pressure drops, and the spray angle is increased with larger recess ratios. Besides, there is a low oscillation frequency at which the self-oscillation phenomenon is activated. The smaller gaseous core sizes and shorter recess lengths could promote self-oscillation. The required liquid flow rate for the self-oscillation phenomena could be raised by increasing the gaseous flow rate, while the self-oscillation frequency hardly varies with it.